Highly efficient cuprous complexes with thermally activated delayed fluorescence and simplified solution process OLEDs using the ligand as host. Issue 6 (19th December 2014) - Chen, Xu-Lin; Lin, Chen-Sheng; Wu, Xiao-Yuan; Yu, Rongming; Teng, Teng; Zhang, Qi-Kai; Zhang, Qing; Yang, Wen-Bing; Lu, Can-Zhong
Abstract : Two highly emissive cuprous complexes with TADF were synthesized. The ligand was used both as a ligand to form the emissive cuprous complex and as a host matrix for the formed emitter in a solution-processed OLED. Abstract : Two strongly luminescent complexes, [Cu(czpzpy)(PPh3 )]BF4 (1 ) and [Cu(czpzpy)(POP)]BF4 (2 ), bearing a new carbazole-based diimine ligand (czpzpy = 2-(9 H -carbazolyl)-6-(1 H -pyrazolyl)pyridine, PPh3 = triphenylphosphine, and POP = bis[2-(diphenylphosphine)phenyl]ether) were synthesized and characterized. Complex2 emits intense thermally activated delayed fluorescence (TADF) with high photoluminescence quantum yields (PLQYs) of up to 0.98 at room temperature in the solid state. A highly efficient solution-processed OLED, with an emissive layer was spin-coated using a mixture of the diimine ligand czpzpy and the starting material, [Cu(CH3 CN)2 )(POP)]BF4, was fabricated with peak efficiencies of 6.36% (external quantum efficiency, EQE) and 17.53 cd A −1 (current efficiency, CE) and a maximum brightness of 3251 cd m −2 . These performances are nearly identical to those of the device whose emissive layer was comprised of complex2 and czpzpy, indicating that this simplified process, which omits the preparation and purification of the emissive complex, is practicable in preparing efficient solution-processed OLEDs. In this approach, czpzpy, which bears a carbazole unit, was used both as a ligand to form the emissive cuprous complex and as a host matrix for the formed emitter.